Translation and Culture: The Change of Cultural Atmosphere in the Translated Version of Ahmad Tohari’s “The Red Bekisar” - Astari Astari (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
This study is conducted in order to discover the difference between the original text, Bekisar Merah, and the translated text, the Red Bekisar. The analysis process and sample gathering will be using Peter Newmark’s concept in translating and culture, while the analysis to reveal the use domestication in the translated text is supported by the definition stated by Hannun Kemppanen.